PENGARUH LITERASI KEUANGAN SYARIAH DAN KEPERCAYAAN TERHADAP KEPUTUSAN NASABAH MEMILIH BANK SYARIAH - Diva Alexsa Putri; Suci Novia Audira (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This qualitative library research analyzes the influence of Sharia financial literacy and customer trust on bank Sharia selection decisions in Medan, North Sumatra, examining 278 credible documents from 2018-2025. Key findings confirm critically low Sharia literacy in Medan (5.9% vs national 9.47%) with mudharabah (78%) and murabahah (85%) understanding gaps, 18.7% trust erosion post-2023 panic withdrawal, and lagging Sharia banking penetration (5.2% vs 7.38% national) with 23.4% churn rate. Structural model Literacy (β=0.333)→ Trust(β=0.468)→ Decision(β=0.378)  proven significant (R²=0.47) via 23 SEM meta-analysis studies, exacerbated by Batak "guaranteed profit" culture (41%) and digital gap (28% vs 73%). Recommendations include "Guaranteed Mudharabah Profit", Medan Sharia Village program, and 50% mobile banking penetration (2027) for +4.8% growth. Theoretical contribution extends Ajzen's TPB with Sharia trust and non-Java context.